Heterogeneous Appearance of Central Nervous System Involvement in Malignant Mixed Müllerian Tumors - Könnecke, Helen K.; Rushing, Elisabeth J.; Neidert, Marian Christoph; Reimann, Regina; Regli, Luca; Bozinov, Oliver; Burkhardt, Jan-Karl (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Involvement of the central nervous system (CNS) is rarely described in malignant mixed Müllerian tumors (MMMTs). Only four intracranial and two spinal cases have been published to date. Here we report two more cases with heterogeneous clinical, radiologic and pathologic features and summarize the available contemporary literature. One patient presented with aphasia due to an intra-axial contrast-enhanced left temporal lesion with marked perifocal edema. After surgical resection, histology showed collections of small uniform tumor cells embedded in a myxoid matrix and compartmentalized by connective tissue septations, consistent with an MMMT. The other patient presented with trigeminal/tongue hypesthesia and double vision accompanied by left radiculopathy and paresis. Magnetic resonance imaging MRI revealed an extraaxial lesion at the petrous tip with mild perifocal edema and multiple small intradural contrast-enhancing lesions of the conus and cauda medullaris. Histologic examination of the intracranial lesion showed a mainly papillary architecture, also consistent with MMMTs. The spinal lesions were not excised, and both patients received adjuvant radiochemotherapy. The first patient died 3 months and the second patient 12 months after surgery. As illustrated by the heterogeneous clinicopathologic features of our two cases as well as the reviewed literature, CNS metastasis of MMMTs is diagnostically challenging, shows a variable outcome, and thus requires individualized treatment. In the present cases and CNS metastases reported to date, a higher histologic ratio of sarcomatous to epithelial components portends a worse outcome.
Keywords: malignant mixed Müllerian tumor; central nervous system metastasis; neurosurgical resection